"Dedicated to being healthy": Young adults' deployments of health-focused cultural capital. (January 2022) - Mollborn, Stefanie; Modile, Adenife
Abstract: Performances of "health" through diet, exercise, and body size are an increasingly important form of cultural capital transmitted to children. Yet less is known about how socioeconomically privileged young people internalize and deploy that capital or how those less privileged manage their relative lack of capital. How does health-focused cultural capital acquired in childhood shape socioeconomic inequalities, health behaviors, and understandings of health in young adulthood? Our analysis of 113 interviews found that health-focused cultural capital acquired in early life reinforced young adults' socioeconomic and health advantages by helping them claim discipline and morality on the basis of their health behaviors and body size. Two key phenomena tended to be present among our many socioeconomically privileged but not our fewer less privileged participants: family socialization into classed diet- and exercise-related health behaviors resulting in a classed appearance of health (despite less-than-ideal behaviors), and cohesive life course narratives linking these behaviors to hard work and moral worth. Less socioeconomically privileged participants' understandings of health and healthy behaviors were different, rarely linking health to worthiness and discipline. To understand the intergenerational transmission of socioeconomic attainment and health in US society, we must consider how behaviors and group-based norms, identities, and understandings of health coalesce in classed health lifestyles that convey cultural capital. Highlights: Class-advantaged young adults acquired health-focused cultural capital in childhood. Childhood diet and exercise behaviors resulted in a classed appearance of health. Young adults' narratives linked these behaviors to hard work and moral worth. Less advantaged young adults rarely linked health to worthiness and discipline. These classed health lifestyle behaviors and narratives can perpetuate inequalities.